(untitled) (Asian Journal of Social Science Studies, 2022)
China’s maritime traffic safety law has enforced for thirty years since 1984 and has not experienced revision, but affected by subjective and objective factors, maritime traffic safety legislation has long ignored the sight of the international law, combined with the great changes in international shipping situation and the maritime traffic safety order, leading to the urgent revision of the old law. The new law came into force in September 2021. As an essential code in the field of maritime law, the United Nations Convention on the Law of the Sea returns to the newly revised Haian Law, which is conducive to China to fulfill its obligations and international responsibilities for relevant international conventions and promote the construction of China’s "maritime power" policy. By comparing the prominent differences between the new law and the old law, this paper aims to specify the responses to the Convention in this law, reflect the return of the Convention in the new law, and make certain comments on the new changes of the law, as well as make responses to some criticisms toward this revision in the international community, and finally summarize the significance of the revision in the national strategic level.